Private and communal lands? The ramifications of tenure ambiguity and regional integration for tenure formalization and its consequences in northern Bolivia. Issue 1 (February 2014) - Perz, Stephen; Barnes, Grenville; Shenkin, Alexander; Rojas, Daniel; Vaca, Carlos
Major integration initiatives such as large-scale infrastructure projects are moving forward in Latin America, creating the conditions theorized by the 'evolutionary theory of land rights' (ETLR) for the shift from communal to private individual tenure. This however assumes a clear distinction between communal and private individual tenure that avoids ambiguities such as those arising from contrasts between de jure tenure rights and de facto practices. We take up these issues by focusing on northern Bolivia, an ambiguous case because groups of families with individual land claims recently received communal titles as 'independent communities'. This has occurred in areas near a major market integration initiative, the Inter-Oceanic Highway, which has recently been paved. We draw on a survey of households in putatively communal lands in northern Bolivia to evaluate the claims of the ETLR concerning regional integration and formalization of private claims and its consequences. We find evidence of practices consistent with private individual tenure, but they are not related to market integration. Further, indications of formalization of private individual rights do not lead to the outcomes anticipated by the ETLR. These findings call for additional comparative work on integration and tenure.